2012
DOI: 10.1159/000339173
|View full text |Cite
|
Sign up to set email alerts
|

Retinal Microvascular Signs Are Associated with Chronic Kidney Disease in Persons with and without Diabetes

Abstract: Background/Aims: In persons with diabetes, retinal microvascular abnormalities are associated with chronic kidney disease (CKD). However, it is not clear if the same relationship applies in persons without diabetes. Methods: We examined 2,971 participants from a population-based study (240 with, 2,731 without diabetes). Retinal photographs were masked graded for retinal microvascular signs, and CKD was defined as estimated glomerular filtration rate (eGFRMDRD) <60 ml/min/1.73 m2. Results:… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
25
1
4

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(35 citation statements)
references
References 54 publications
3
25
1
4
Order By: Relevance
“…With regard to retinopathy, previous studies have found a positive relationship with CKD in non-diabetic persons [30,31,34,35]. Our results indicate that the cross-sectional association between reduced GFR and retinopathy extends into the normal GFR range and that it is independent of microalbuminuria (table 3).…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…With regard to retinopathy, previous studies have found a positive relationship with CKD in non-diabetic persons [30,31,34,35]. Our results indicate that the cross-sectional association between reduced GFR and retinopathy extends into the normal GFR range and that it is independent of microalbuminuria (table 3).…”
Section: Discussionsupporting
confidence: 73%
“…There are divergent results of investigations of the association between renal vessel diameters and CKD defined as eGFR crea <60 ml/min/1.73 m 2 . Whereas some studies have found an association between narrow retinal arteries or wider retinal veins and the odds of having CKD, others have not [30,31]. …”
Section: Discussionmentioning
confidence: 99%
“…Studying these retinal vascular caliber changes provides insight into parallel pathology that may occur in the systemic micro- and macro-circulations, with retinal arteriolar narrowing strongly associated with angiographically defined coronary artery occlusion,[12] reduced myocardial perfusion,[13] and greater aortic stiffness. [14] Wider venules are associated with chronic kidney disease,[15], [16] aortic calcification[17] and progression of cerebral small vessel disease [18]. Among people with diabetes, wider venular caliber is directly related to the presence and severity of diabetic retinopathy [19], [20]…”
Section: Introductionmentioning
confidence: 99%
“…These changes are also observed in the paediatric and adolescent population [ 52 -54 ]. Retinal microvascular signs such as venular dilatation are associated with CKD both in the presence and absence of diabetes, thus reinforcing the link between renal and retinal microvasculature independently of diabetes [ 55 ].…”
Section: Investigating Arterial Disordersmentioning
confidence: 72%